Evaluation of neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, and lymphocyte to monocyte ratio in patients with cellulitis - Ince,Nevin (2020)
SUMMARY OBJECTIVE Cellulite infection is a non-necrotizing inflammation of the skin and subcutaneous tissue and is one of the most common reasons for admission to hospital. This retrospective study aimed to investigate the Neutrophil to Lymphocyte Ratio (NLR), Platelet to Lymphocyte Ratio (PLR), and Lymphocyte to Monocyte Ratio (LMR) in patients with cellulitis. METHODS In our study, we retrospectively analyzed 96 patients with cellulitis and 98 age- and sex-matched healthy controls. The study and control groups were compared regarding NLR, PLR, and LMR.0.001). When patients with cellulitis were divided into two groups, i.e., ≥65 years and <65 years, a statistically significant difference was noted in the NLR and LMR values (p < 0.05). In the ROC curve analysis, NLR had the highest discriminative power in distinguishing between cellulitis and healthy controls (AUC = 0.950, 95% CI: 0.920–0.979, p < 0.001; 91.6% sensitivity and 89.8% specificity). CONCLUSION NLR was significantly higher in differentiating cellulite and in patients older than 65 years. Larger, prospective studies are required to determine its usefulness in assessing differential diagnosis and prognosis in cellulitis patients.